Aligning Information Technology Governance with Business Goals Using the COBIT 2019 Framework: A Case Study of a Innovation Consultancy Firm - Mokodaser, Wilsen Grivin; Mambu, Joe Yuan; Koapaha, Hartiny; Lompoliu, Erienika (CogITo Smart Journal, 2024)
Technological advancements have ushered the world into a new era, particularly in the realm of information. In this context, information technology is considered a crucial tool to support and enhance corporate management, enabling companies to compete in the market. One common approach to managing information technology is by using IT governance frameworks such as COBIT (Control Objectives for Information and Related Technology) 2019. To date, there has been no research or evaluation conducted on the IT performance of Meet Ventures, Pte. Ltd., leaving the maturity level of information technology implementation in the company unclear. This project aims to explore the use of information systems and information technology at Meet Ventures, Pte. Ltd. in managing their operations and data. The project's approach involves a literature study on COBIT 2019 design factors. Based on the application of COBIT 2019, the prioritized objectives identified are BAI03 – Manage Solutions Identification and Build, BAI06 – Manage IT Changes, and MEA01 – Monitor, Evaluate, Assess Performance and Conformance. The assessment of various design factors in COBIT 2019 indicates that Meet Ventures, Pte. Ltd. has a strong focus on innovation, differentiation, and customer service. They also demonstrate a commitment to legal compliance and external regulations, a customer service culture, and effective risk management.